Positive Affirmation In Education Of Youth Characters In The Millennal Era - Amaliaa, Ulfa (Universitas Mercu Buana Yogyakarta, 2020)
The fundamental problem in the current 4.0 industrial revolution era is related to character education in adolescents in facing challenges and changes in a very rapid era. The high need to depend on the internet that is very high changes the pattern of social interaction in the real world switching through social media. The development of this era would not only have a negative impact but also bring positive change, but the mental readiness and strength of adolescent characters really need to be formed through positive affirmations which are actually very easy to do but are often ignored because they are lulled by pseudo exposure on social media. This article reviews the importance of habituation with positive affirmations which basically gives an influence on mind to hypnotize oneself through positive words or sentences so that if it is done regularly and continuously, it will be able to bring big changes to the teenagers mindset who tend to be irrational, to be rational. The transition will certainly provide positive energy to the character of adolescents, which is manifested by the ability to be wise in using technology in the present and the future.Â Â